1986
DOI: 10.2134/agronj1986.00021962007800040023x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐induced Zinc Deficiency in Wheat on Residual Phosphorus Plots1

Abstract: One-time heavy application of P on certain soils can provide sufficient available P to sustain crop production over a period of several years, but may cause Zn nutritional problem for crops. A field study was conducted to determine tbe effect of applied Zn on wheat (Triticum aestivum L.) grown on residual P plots and identify tbe mechanism of P X Zn interaction. This study was conducted in 1984 in a continuous wheat system on a clayey, mixed, frigid Typic Hyploboroll soil that bad received 0, 80, and 160 kg P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
21
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 18 publications
4
21
0
1
Order By: Relevance
“…According to Karblane [11], and He and Singh [12], it was showed that phosphate inhibited Cd uptake in the pot-culture studies with different corps. On the contrary, phosphate has also been shown to increase plant uptake [13]. Moreover, interaction of Cd and phosphate was investigated under hydroponics.…”
Section: Introductionmentioning
confidence: 99%
“…According to Karblane [11], and He and Singh [12], it was showed that phosphate inhibited Cd uptake in the pot-culture studies with different corps. On the contrary, phosphate has also been shown to increase plant uptake [13]. Moreover, interaction of Cd and phosphate was investigated under hydroponics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, supplementing Fe uptake has been found to reduce stress caused by high Zn (Kaya and Higgs 2001). Although the mechanism is not entirely understood, high amounts of phosphorus (P) have been found to reduce Zn activity in plant tissue, even to the point of inducing Zn deficiency (Singh et al 1986). Iron oxides, when applied to the soil, have been shown to reduce uptake of all metals by immobilizing them in the soil (Lombi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The overapplication of P and P accumulation in soils has the potential to create deficiencies and toxicities of other nutrients as well. For example, several research studies have shown that Zn deficiencies can be induced with excessively high concentrations of P fertilizer in the soil (Singh et al, 1988;Cakmak and Marschner, 1986;Singh et al, 1986). Manure additions also tend to have a liming effect in most soils as large amounts of Ca and Mg are added with the manures (Eghball et al, 2004;Mokolobate and Haynes, 2002).…”
mentioning
confidence: 99%